The dragons and the snakes: how the rest learned to fight the West - Kilcullen, David (Oxford scholarship online Political Science, 2020)
This text applies concepts from evolutionary science and military innovation to explore how state and nonstate adversaries of the Western powers have learned to defeat (or render irrelevant) the model of high-tech, expensive, precision warfare pioneered by the United States in 1991 and globally dominant since. The book begins with a historical overview of the period since the Cold War, framed by CIA Director James Woolsey's 1993 comment that 'we have slain a large dragon' (the Soviet Union) 'but now we find ourselves in a jungle filled with a bewildering variety of poisonous snakes, and in many ways the dragon was easier to keep track of.'